Implementation Of Macromedia Flash-Based Parabola Virtual Practicum Application in Growing Science Process Skills During the Covid-19 Pandemic - Eko Wiyanto; Agus Suyatna; Chandra Ertikanto (Postgraduate, University of Mataram, 2022)
This study aims to determine the effect of the implementation of a virtual parabolic motion practicum based on macromedia flash on the growth of students' science process skills. The research was carried out at SMA Negeri 2 Bandar Lampung, with a population of all students in class X MIPA, and a sample of class X MIPA 1 as many as 36 students with purposive sampling technique. By using a research design that is one group pretest-posttest. The data analysis technique used is the normality test, the two related sample test, and the N-Gain test. The results showed that there was a difference between the average pretest and posttest values of 7.00 with an N-Gain score of 0.2 with low criteria. Based on the results of the study, it can be concluded that the implementation of a virtual parabolic motion practicum based on macromedia flash has an effect on growing Science Process Skills in students